STUDENTS’ LIVED EXPERIENCES OF COMMUNICATION AUDITS: A PHENOMENOLOGICAL STUDY OF A UNIVERSITY STUDENT ORGANIZATION - Kendy Ergi Ade Dea; Syafrina Rahma Harahap; Sabrina Leyda Rahmiarini (Academic Solution Publisher, 2026)
This study aims to understand the experiences and meanings constructed by Communication Science students at UIN Sumatera Utara (UINSU) Medan regarding communication audits within the organization of the Communication Science Student Association (HMJ Ilmu Komunikasi). The study employs a qualitative method with Edmund Husserl’s phenomenological approach, which places individuals’ conscious experiences as the primary source for understanding reality. Informants were selected purposively from HMJ administrators who were directly involved in organizational activities. Data were collected through semi-structured in-depth interviews and observations, and subsequently analyzed using Clark Moustakas’ phenomenological analysis, including the stages of horizonalization, textual description, and structural description. Data validity was ensured through source triangulation and technique triangulation. The findings reveal that students perceive communication audits as a process of evaluating the effectiveness of information flow, work-program coordination, and the quality of communication relationships among organizational members. This understanding is not solely derived from academic knowledge but is also shaped by direct experiences in organizational life, including encounters with communication barriers such as inter-divisional miscommunication, delayed responses, and unequal information distribution. This study contributes to the field of organizational communication by positioning communication audits as a phenomenon subjectively interpreted by members of student organizations, rather than merely as a managerial evaluation instrument.